Evolución de la relación entre texto e imagen en la poesía chilena: Vicente Huidobro, Nicanor Parra y Juan Luis Martínez - Cifuentes-Aldunate, Claudio (Diálogos Latinoamericanos, 2018)
The present reflection focuses on the phenomenon of writing and image. It is an evolutionary revision within the Chilean poetry from the moment in which the non-scriptural image made its appearance through the calligrams of Vicente Huidobro to later give way to the artifacts of Nicanor Parra arriving, finally, at the Installations of objects in “box-books” by Juan Luis Martínez. The present study addresses the type of relationship that evolves between image and text from the image “within” the text, passing through the text ‘within’ the image and, finally, arriving at/to/until the object-image. The “absent” text, which gives it meaning, arises as a responsibility of the reader. The reflection addresses the rejection of “pure writing” as an element that eradicates these texts from the metaphysics of the presence of logos, especially in the first two cases (Huidobro and Parra), while there would seem to be an ambiguity in Martínez, insofar as he is not giving all the elements necessary (for the reader) to construct the sense. Martinez encourages the reader to take charge of giving meaning to the elements that he provides (antilogocentric gesture), and, at the same time, he delivers the elements in his “box-books” which are impregnated with a beloved “authenticity”(hyperlogocentric gesture). This is why it is possible to speak of ambiguity.